2017
DOI: 10.3390/bioengineering4020027
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian Trajectories to Predict the Formation of Population Heterogeneity in Large-Scale Bioreactors

Abstract: Successful scale-up of bioprocesses requires that laboratory-scale performance is equally achieved during large-scale production to meet economic constraints. In industry, heuristic approaches are often applied, making use of physical scale-up criteria that do not consider cellular needs or properties. As a consequence, large-scale productivities, conversion yields, or product purities are often deteriorated, which may prevent economic success. The occurrence of population heterogeneity in large-scale producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…The consequence is that every time when a new position of a cell is computed (based on the computed fluid flow), a random side step is added that mimics the effect of the turbulence. By storing the positions of the cells as function of time, the 'lifeline' of each simulated cell is recorded (Enfors et al, 2001;Haringa et al, 2016;Kuschel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The consequence is that every time when a new position of a cell is computed (based on the computed fluid flow), a random side step is added that mimics the effect of the turbulence. By storing the positions of the cells as function of time, the 'lifeline' of each simulated cell is recorded (Enfors et al, 2001;Haringa et al, 2016;Kuschel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The computational demand is considerable since O (10 5 +) parcels may be required for a proper representation of the population (Haringa, Noorman, & Mudde, ), but accounting for additional pools and pool interaction is straightforward, thus averting the shortcomings of the Eulerian approach. An additional benefit is that the extra‐ and intracellular status of each parcel can be tracked, providing so‐called “lifelines” (Haringa et al, ; Kuschel, Siebler, & Takors, ; Lapin et al, , ; Y. Liu et al, ) and providing information on the environment through the organism's eyes. With this methodology in place, simulations can be utilized as an integral part of the bioreactor design cycle (Figure ), starting with assessment of the large‐scale design (Figure a), downscaling and analysis of the organism's response (Figure b), including said response in the simulation (Figure c) and in‐silico improvement of the design (Figure d).…”
Section: Through the Organism's Eyes: The Interaction Between Hydrodymentioning
confidence: 99%
“…A comparison of the cases also provided valuable insights into how substrate gradients manifest, depending on the substrate uptake characteristics and mixing behavior. McClure, Kavanagh, Fletcher, and Barton () studied exposure to excess sugar concentrations in a bubble column, whereas Kuschel et al () studied the presence of different regimes in replication behavior of P. putida in an industrial reactor. Most recently, Siebler, Lapin, Hermann, and Takors () used the approach to study CO limitations in syngas fermentation with C. Ljungdahlii , indicating 97% of cells experience substrate limitations, and 84% are likely to undergo transcription changes, after stress exposures of more than 70 s. Y. Liu et al () focused on strain‐rate variations observed by plant cells and their influence on viability loss, in what constitutes an evolution of the “Energy dissipation circulation function (EDCF)” method (Jüsten, Paul, Nienow, & Thomas, ).…”
Section: Through the Organism's Eyes: The Interaction Between Hydrodymentioning
confidence: 99%
See 2 more Smart Citations